Peculiar behavior of MWW materials in aldol condensation of furfural and acetone - Kikhtyanin, Oleg; Chlubná, Pavla; Jindrová, Tereza; Kubička, David (Dalton transactions (Cambridge, England, 2014)
MWW family of different structural types (MCM-22, MCM-49, MCM-56 and MCM-36) was used as catalysts for aldol condensation of furfural and acetone studied in a batch reactor at 100 °C, autogenous pressure and a reaction time of 0-4 h. To establish a relation between physico-chemical and catalytic properties of microporous materials, the samples were characterized by XRD, SEM, N2 adsorption, FTIR and TGA. It was found that the acidic solids possessed appreciable activity in the reaction and resulted in the formation of products of aldehyde-ketone interaction. Surprisingly, MCM-22 and MCM-49, i.e. three-dimensional materials containing internal supercages, exhibited higher activity than two MCM-36 catalysts with two-dimensional character having larger accessible external surface area due to expansion of the interlayer space by swelling and pillaring treatments. Moreover, all MWW family catalysts gave higher conversion than the large-pore zeolite BEA. Nevertheless, furfural conversion decreased rapidly for all the studied materials due to coke formation. Unexpectedly, the deactivation was found to be more severe for MCM-36 catalysts than for MCM-22 and MCM-49, which was attributed to the reaction taking place also in supercages that are protected by 10-ring channels from severe coking. In contrast the cups located on the external surface were coked rapidly.